Pengaruh Guided Imagery terhadap Penurunan Intensitas Nyeri pada Pasien Pasca Operasi: Scoping Review (Inovasi Kesehatan Global, 2026)
Postoperative pain is a prevalent condition encountered by patients after surgical interventions and may negatively influence physical recovery as well as psychological well-being when inadequately managed. Conventional pain management strategies that primarily depend on pharmacological agents may lead to undesirable side effects, thereby emphasizing the importance of complementary non-pharmacological approaches. One intervention increasingly applied in nursing care is guided imagery. This review aimed to systematically evaluate the effectiveness of guided imagery in alleviating pain intensity among postoperative patients. A scoping review methodology was employed, with article identification guided by the PICO framework across national and international academic databases. Eligible studies included full-text research articles published within the past five years, written in either Indonesian or English, and specifically examining the use of guided imagery in postoperative settings. A total of ten studies met the inclusion criteria and were subjected to in-depth analysis. The results consistently demonstrated a significant reduction in pain intensity following the implementation of guided imagery across various surgical procedures, including cesarean delivery, appendectomy, fracture surgery, cholelithiasis, and abdominal operations. The intervention, delivered for 10–20 minutes per session, effectively reduced pain levels from moderate to severe to mild, with statistically significant outcomes (p < 0.05). Moreover, guided imagery was found to enhance patient relaxation, comfort, and psychological stability. These findings indicate that guided imagery represents a safe and effective non-pharmacological nursing intervention that can be integrated into evidence-based postoperative pain management.